Informal Institution Meets Child Development: Clan Culture and Child Labor in China - Can Tang; Zhong Zhao (Global Labor Organization (GLO), 2022)
Using a national representative sample, the China Family Panel Studies, this paper explores the influences of clan culture, a hallmark of Chinese cultural history, on the prevalence of child labor in China. We find that clan culture significantly reduces the incidence of child labor and working hours of child laborer. The results exhibit strong boy bias, and are driven by boys rather than girls, which reflects the patrilineal nature of Chinese clan culture. Moreover, the impact is greater on boys from households with lower socioeconomic status, and in rural areas. Clan culture acts as a supplement to formal institutions: reduces the incidence of child labor through risk sharing and easing credit constraints, and helps form social norms to promote human capital investment. We also employ an instrument variable approach and carry out a series of robustness checks to further confirm the findings.
Keywords: J22; J81; O15; 330; Informal institution; Clan culture; Child labor; China